Impact of hearing protection devices on sound localization performance - Zimpfer, Véronique; Sarafian, David (Frontiers in Neuroscience, 2014)
Hearing Protection Devices (HPDs) can protect the ear against loud potentially damaging sounds while allowing lower-level sounds such as speech to be perceived. However, the impact of these devices on the ability to localize sound sources is not well known. To address this question, we propose two different methods: one behavioral and one dealing with acoustical measurements. For the behavioral method, sound localization performance was measured with, and without, HPDs on 20 listeners. Five HPDs, including both passive (nonlinear attenuation) and three active (talk-through) systems were evaluated. The results showed a significant increase in localization errors, especially front-back and up-down confusions relative to the “naked ear” test condition for all of the systems tested, especially for the talk-through headphone system. For the acoustic measurement method, Head-Related Transfer Functions (HRTFs) were measured on an artificial head both without, and with the HPDs in place. The effects of the HPDs on the spectral cues for the localization of different sound sources in the horizontal plane were analyzed. Alterations of the Interaural Spectral Difference (ISD) cues were identified, which could explain the observed increase in front-back confusions caused by the talk-through headphone protectors.